STAKEHOLDER ANALYSIS IN THE ASN LEARNING PROGRAM AT THE HUMAN RESOURCES DEVELOPMENT AGENCY OF EAST JAVA PROVINCE - Didiek Dwiyanto; Andi Taufik; Chusaini Mustas (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
ASN in Indonesia is given the opportunity to gain knowledge in accordance with competency development planning at Government Agencies whose purpose is to develop competencies to support the implementation of tasks. Therefore, the East Java Provincial Government together with the Ministry of State Apartur Empowerment and Bureaucratic Reform and the State Administration Institute agreed to form the